Background ADC calibration in digital domain - Cheongyuen Tsang; Yun Chiu; Vanderhaegen, J.; Hoyos, S.; Chen, C.; Brodersen, R.; Nikolic, B. (2008 IEEE Custom Integrated Circuits Conference, 2008)
A 100 MS/s pipelined ADC is digitally calibrated by a slow SigmaDelta ADC using a least-mean-square (LMS) algorithm. Both linear and nonlinear memoryless residue gain errors of the pipeline stages are adaptively corrected. With a 411 kHz sinusoidal input, the peak SNDR improves from 28 dB to 59 dB and the SFDR improves from 29 dB to 68 dB. The complete 0.13 mu ADC SoC occupies a die size of 3.7 mm times 4.7 mm, and consumes a total power of 448 mW.